The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1038/s41598-023-31180-z
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing genomic characteristics across an RNA-Seq based reference landscape of normal and neoplastic brain

Abstract: In order to better understand the relationship between normal and neoplastic brain, we combined five publicly available large-scale datasets, correcting for batch effects and applying Uniform Manifold Approximation and Projection (UMAP) to RNA-Seq data. We assembled a reference Brain-UMAP including 702 adult gliomas, 802 pediatric tumors and 1409 healthy normal brain samples, which can be utilized to investigate the wealth of information obtained from combining several publicly available datasets to study a si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This landscape is made up of multiple clusters of different sizes, all of which are composed of a mix of the 13 datasets with the exception of the HKU/UCSF dataset (GSE212666) for which a minor subset of patients forms two, small unique clusters (11% of HKU/UCSF dataset) (Figure 1B). In addition to UMAP, we explored other dimension reduction techniques (Principal Component Analysis (PCA) and t-distributed Stochastic Neighbor Embedding (tSNE)) and found that UMAP better distinguished clusters that showed differences in clinical and genomic features (Figures S1B, S1C) 27 . The collection of tumor samples included fresh frozen tissue as well as Formalin-Fixed Paraffin-Embedded tissue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This landscape is made up of multiple clusters of different sizes, all of which are composed of a mix of the 13 datasets with the exception of the HKU/UCSF dataset (GSE212666) for which a minor subset of patients forms two, small unique clusters (11% of HKU/UCSF dataset) (Figure 1B). In addition to UMAP, we explored other dimension reduction techniques (Principal Component Analysis (PCA) and t-distributed Stochastic Neighbor Embedding (tSNE)) and found that UMAP better distinguished clusters that showed differences in clinical and genomic features (Figures S1B, S1C) 27 . The collection of tumor samples included fresh frozen tissue as well as Formalin-Fixed Paraffin-Embedded tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Gene expression values from combined datasets were normalized and converted to units of log2 transcripts per million (log2(TPM+1)) 26 . Uniform Manifold Approximation and Projection (UMAP), a dimensionality reduction method, was applied on normalized counts from 19979 protein-coding genes to create the meningioma reference landscape 27 . UMAPs were constructed using the R package "umap" (https://cran.r-project.org/web/packages/umap/index.html).…”
Section: Rna-seq Data Processing and Visualizationmentioning
confidence: 99%
“…2 g), with the higher expression in brain spinal cord. Among these lncRNAs, only one - LINC01445 – has been previously studied, as it has been found fused to EGFR in 17.7% of adult IDH-wt glioblastoma 62 . Interestingly, the green module resulted unconnected to the rest of the network: as network edges represent co-expression relationships between genes, such a scenario indicates possible features (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Table 4 presents the summary of Review 2, including KOS adopted in the EHR and the key contribution. Eleven studies were analyzed in Review 3, of each the studies (12,13,14,15,16) use GO, work (17) used both GO and NCIt, works (18,19) refer to the NCIt, and other three works are undefi ned regarding the use of KOS.…”
Section: Resultsmentioning
confidence: 99%
“…In reference (18) a modified Delphi approach is used to guide the Pediatric Cancer Data gathering. Work (15) uses GO in the visualization of genomic characteristics and reference (16) uses GO to reveal recurrent genetic and transcriptomic signatures.…”
Section: Discussionmentioning
confidence: 99%